Natural killer cells suppress cancer metastasis by eliminating circulating cancer cells - Vyas, Maulik; Requesens, Marta; Nguyen, Thao H.; Peigney, Domitille; Azin, Marjan; Demehri, Shadmehr (Frontiers in Immunology, 2023)
Despite significant advances in cancer treatment, the metastatic spread of malignant cells to distant organs remains a major cause of cancer-related deaths. Natural killer (NK) cells play a crucial role in controlling tumor metastasis; however, the dynamics of NK cell-mediated clearance of metastatic tumors are not entirely understood. Herein, we demonstrate the cooperative role of NK and T cells in the surveillance of melanoma metastasis. We found that NK cells effectively limited the pulmonary seeding of B16 melanoma cells, while T cells played a primary role in restricting metastatic foci growth in the lungs. Although the metastatic foci in the lungs at the endpoint were largely devoid of NK cells, they played a prominent role in promoting T cell recruitment into the metastatic foci. Our data suggested that the most productive interaction between NK cells and metastatic cancer cells occurred when cancer cells were in circulation. Modifying the route of administration so that intravenously injected melanoma cells bypass the first liver passage resulted in significantly more melanoma metastasis to the lung. This finding indicated the liver as a prominent site where NK cells cleared melanoma cells to regulate their seeding in the lungs. Consistent with this notion, the liver and the lungs of the tumor-bearing mice showed dominance of NK and T cell activation, respectively. Thus, NK cells and T cells control pulmonary metastasis of melanoma cells by distinct mechanisms where NK cells play a critical function in shaping T cell-mediated in situ control of lung-seeded cancer cells. A precise understanding of the cooperative role of NK and T cells in controlling tumor metastasis will enable the development of the next generation of cancer immunotherapies.